Trends in India's Public Spending on Elementary Education: Challenges and Solutions for India's Higher Education System (Journal of Advances and Scholarly Researches in Allied Education, 2020)
For a developing nation like India, where social and economic progress go hand in hand,education is crucial. It often includes undergraduate, graduate, and doctorate programmes in additionto pre- and post-doctoral degrees. It also has a significant impact on the process of turning outeducators. Consequently, it is necessary for survival. As a result, this page provides information aboutcurrent educational developments in India as well as problems and solutions. The research wasconducted in a review environment using material found via keyword searches on search engines suchPubMed Google Scholar. Even while higher education has expanded significantly over the last severalyears, it is still under risk because of issues such as the quota system and privatisation, among others.Therefore, a variety of strategies must be developed to enhance India's higher education system.